2018
DOI: 10.1182/bloodadvances.2018020305
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of low allelic ratio FLT3-ITD and NPM1 mutation in acute myeloid leukemia

Abstract: In the opinion of the European LeukemiaNet (ELN), nucleophosmin member 1 gene mutation (NPM1 mut)–positive acute myeloid leukemia (AML) with an fms-like kinase 3-internal tandem duplication (FLT3-ITD) allele ratio (AR) <0.5 (low AR) has a favorable prognosis, and allogeneic hematopoietic stem cell transplant (allo-HSCT) in the first complete remission (CR1) period is not actively recommended. We studied 147 patients with FLT3-ITD gene mutation–positive AML, dividing them into those with low AR and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 35 publications
(43 reference statements)
5
69
1
Order By: Relevance
“…Besides, some studies indicated that allo-HSCT improves the prognosis in NPM1 mutated AML with FLT3-ITD low AR. [19][20][21] Moreover, Patel et al 23 reported that high variant allele frequency of NPM1 predict poor outcomes in de novo AML, even after undergoing hematopoietic stem cell transplantation. And the effect of high NPM1 variant allele frequency on prognosis was not affected by the level of FLT-ITD AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, some studies indicated that allo-HSCT improves the prognosis in NPM1 mutated AML with FLT3-ITD low AR. [19][20][21] Moreover, Patel et al 23 reported that high variant allele frequency of NPM1 predict poor outcomes in de novo AML, even after undergoing hematopoietic stem cell transplantation. And the effect of high NPM1 variant allele frequency on prognosis was not affected by the level of FLT-ITD AR.…”
Section: Discussionmentioning
confidence: 99%
“…However, this risk classification on FLT3-ITD and NPM1 double mutated AML was not accepted by some clinicians, and several studies provided evidence that this type of AML is with unfavorable risks. [16][17][18][19][20][21] What is the optimal treatment for AML FLT3-ITD+/NPM1+ patients is also under investigation. In this study, we retrospectively analyzed the clinical features and risk factors of AML FLT3-ITD+/NPM1+ , and discussed whether hematopoietic stem cell transplantation is necessary after complete remission (CR).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ELN‐2017 system includes CN‐AML patients with mutated NPM1 and FLT3 ‐ITD low in addition to those with mutated NPM1 and wild‐type FLT3 . However, we and others reported that FLT3 ‐ITD low has an impact on the long‐term prognosis, as for FLT3 ‐ITD high , in Japanese AML patients …”
Section: Clinical Significance Of Flt3 Mutationsmentioning
confidence: 99%
“…FMS-like tyrosine kinase 3 (FLT3) internal tandem duplication (FLT3-ITD) or tyrosine kinase domain (FLT3-TKD) gene mutations are encountered in around 30% of acute myeloid leukemia (AML) Japanese study reported that performing allo-SCT in CR1 significantly improves the outcome in these patients, irrespective of the FLT3-ITD allele ratio [12]. Unfortunately, patients with FLT3-ITD mutation still carry a poor prognosis after allo-SCT because of higher rates of early relapse and the lack of response to chemotherapy in the salvage setting [13,14].…”
Section: Introductionmentioning
confidence: 99%